2020
DOI: 10.1097/jhm-d-19-00177
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between “Leader in LGBT Healthcare Equality” Designation and Hospitals’ Patient Experience Scores

Abstract: EXECUTIVE SUMMARY An increasing number of lesbian, gay, bisexual, and transgender (LGBT) individuals openly acknowledge their identity; however, the fear of discrimination prevents many from seeking healthcare—an issue challenged by a lack of culturally competent LGBT healthcare providers. With more than 4% of American adults identifying as LGBT individuals, greater attention to their needs is imperative to improve care and access for this population. This study examined organizational and market f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…To date, there has been limited empirical analysis regarding the influence of health organizations' cultural competency for providing patient-centric care for the LGBTQ community. DiLeo et al 9 were the first to study the relationship between hospitals' participation in the HEI and their patient experience outcomes, measured by their Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scores. In their cross-sectional study, DiLeo et al found that HEI Leader–designated hospitals reported significantly higher overall hospital rating patient experience scores indicating “likelihood to recommend” as compared with non-HEI Leader hospitals and that certain hospital organizational characteristics and market factors demonstrated a positive association with being a “LGBTQ Healthcare Equality Leader” (formerly “Leader in LGBT Healthcare Equality;” p. 373).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there has been limited empirical analysis regarding the influence of health organizations' cultural competency for providing patient-centric care for the LGBTQ community. DiLeo et al 9 were the first to study the relationship between hospitals' participation in the HEI and their patient experience outcomes, measured by their Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scores. In their cross-sectional study, DiLeo et al found that HEI Leader–designated hospitals reported significantly higher overall hospital rating patient experience scores indicating “likelihood to recommend” as compared with non-HEI Leader hospitals and that certain hospital organizational characteristics and market factors demonstrated a positive association with being a “LGBTQ Healthcare Equality Leader” (formerly “Leader in LGBT Healthcare Equality;” p. 373).…”
Section: Introductionmentioning
confidence: 99%
“…7 Before the Supreme Court's 2015 Obergefell v. Hodges decision that legalized marriage equality nationwide, a Gallup survey reported that 7.9% of LGBTQ adults were in same-sex marriages and 2 years after the decision, the percentage increased to 10.2%. 8 Given the growing LGBTQ community, DiLeo et al 9 describe the importance of evaluating hospitals' proactiveness for serving these populations to determine how it relates to the patient experiences. Thus, in 2007, the Human Rights Campaign Foundation (HRC) introduced the Healthcare Equality Index (HEI) for the purpose of evaluating healthcare facilities' policies and practices related to the equity and inclusion of their LGBTQ patients, visitors, and employees and formally recognizing those facilities that lead the field in LGBTQ inclusion based on scored criteria.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients report higher satisfaction when health systems are LGBTQ+ affirming regardless of sexual orientation or gender identity. 42 Moreover, explicit and inclusive visitation policies may improve partner engagement and support for LGBTQ+ patients. 43 LGBTQ+ affirming healthcare providers are also more likely to have explicit employee and patient nondiscrimination policies as well as staff training in LGBTQ+ patient-centered care.…”
Section: Introductionmentioning
confidence: 99%
“…20 At the institutional level, patients report higher satisfaction when health systems are LGBTQ+ affirming regardless of sexual orientation or gender identity. 21 Affirming care practices and explicit nondiscrimination policies may also allow for greater involvement of partners and caregivers in contexts like cancer care, where patients have concerns about disclosing their LGBTQ identity and bringing their partner to appointments. [22][23][24] Conversely, when patients do not feel comfortable disclosing or are not asked 19 about their sexual orientation, gender identity, or sexual behavior, this can lead to inattention to health needs and missed diagnostic screenings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation